BUDAYA SEKOLAH MEMODERASI PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU PNS DI SMP NEGERI SE KECAMATAN PEKALONGAN BARAT (Students' Journal of Economic and Management, 2013)
This study examined the School Culture Moderating the Effect of Competence and Motivation against on PNS Teacher Performance at Junior High School in West Pekalongan Region. Specific purpose of research is to test and analyze How School Culture Moderating the Effect of Competence and Motivation against on Teacher’s Performance. The usefulness of the research is to explain and extend previous research on the influence of the Effect of Competence and Motivation on Teacher’s Performance. The population in this study was teachers of PNS in a Junior High School in West Pekalongan region, amounting to 145 people. In this study using primary data obtained by questionnaires. The research method is using a computerized approach to the SPSS statistical program (Statistics Package for Social Science). The method of data analysis used linear regression with the moderating effects test. The results showed that competence has a positive and significant effect on performance. Motivation has a negative and significant effect on performance. School culture has a positive and significant effect on performance. School culture moderates the effect of competence on performance has a negative and significant effects. School culture moderates the effect of motivation on performance has a negative significant effect. Suggestions that can be recommended in this research is to improve the competence and motivation in carrying out the learning process followed by creating a good school culture can improve the performance of the national education goals can be achieved. Keywords: school culture, competence, motivation, performance and moderation.